Influence of Telmisartan on Pharmacodynamic and Pharmacokinetic Properties of Glimepiride-metformin Combination Using Rodent and Non-Rodent Models - Nagaraju, Beere; Anilkumar, KV (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The present study was planned to evaluate the pharmacodynamic and pharmacokinetic interactions between telmisartan and glimepiride + metformin in single and multiple dose studies using rats and rabbits. Materials and Methods: The blood samples were collected from the rats/ rabbits from retro orbital/ marginal ear vein respectively. The serum glucose, plasma insulin and serum glimepiride were estimated at respective time intervals in all treatment groups. Results: The single and multiple dose treatments of telmisartan alone and combined treatment with glimiperide + metformin does not showed any significant reduction of glucose and elevated insulin levels in normal and diabetic rats and showed synergistic hypoglycemic activity by enhancing blood glucose reduction and peak insulin levels in normal rabbits. The serum glimepiride levels were found to be enhanced with telmisartan single and multiple dose treatments. There is significant increase in the pharmacokinetic parameters of glimepiride like AUC0-∞, AUMC0-t, AUMC0-∞, t1/2, Cmax and MRT and there is a decrease in clearance (Cl) with single and multiple dose treatments of telmisartan. Conclusion: The interactions observed in rabbits (a non rodent model) but not in rats (a rodent model). Hence care must be taken while prescribing telmisartan in combination with glimipiride-metformin.
Keywords: Telmisartan; Glimepiride; Metformin; Pharmacokinetics; Pharmacodynamics